Habits, attitudes, and behavior of refugees and migrants in Serbia concerning oral health - Mandinić, Zoran; Prokić, Aleksandra; Ivanović, Mirjana; Jovanović, Svetlana; Jovičić, Olivera; Beloica, Miloš (Vojnosanitetski pregled, 2022)
Background/Aim. A large number of refugees and migrants have passed through the Republic of Serbia in recent years. Oral health is one of the key indicators of general health. The aim of this study was to investigate self-reported oral health, oral health related habits, nutrition, and the use of dental services among refugees and migrants in Serbia. Methods. A total of 226 migrants participated in the study. Participants were accommodated in the migrant centers Obrenovac and Krnjača in Belgrade, Serbia. All participants were given a questionnaire in order to examine oral health habits, attitudes, and behavior among refugees and migrants. The questionnaire consisted of 29 questions. SPSS 24 statistical software was used to analyze answers from the questionnaire. Results. Out of 226 examinees, 40 were female, and 186 were male. The majority (87.6%) were adults, and 12.4% were children. The results showed that refugees and migrants who spent 200–300 € per month consumed alcohol (33.3%) and tobacco (61.1%) the most. Only 10.8% of men answered they had been to the dentist in Serbia, whereas 35% of women had the same answer (p = 0.000). The research also showed that most women (67.5%) brush their teeth 2-3 times a day, and noticeably fewer men (37.1%) had the same habit. Fluoride supplements were used by 78.7% of examinees. Among the most common reasons for the last visit to the dentist were pain (36.9%) and regular checkups (22.5%). Conclusion. Preservation of oral health of refugees and migrants in Serbia depends on various factors. Improving and preserving the good general and oral health of refugees and migrants should be a public healthcare priority.